Influence of Community Knowledge and Attitudes on Ecotourism Development in Bagek Kembar, Lombok, Indonesia - Putri, Adinda Fitriana; Suana, I Wayan; Hadiprayitno, Gito (Indonesian Journal of Tropical Biology, 2026)
Bagek Kembar mangrove ecotourism area in Cendi Manik Village, Sekotong, West Lombok, Indonesia, is being developed by the local community as an environmental conservation initiative and a sustainable tourism destination. Community participation plays an important role in supporting the success of ecotourism development, especially through the knowledge and attitudes of local residents toward mangrove conservation. This study aims to identify and analyze the influence of community knowledge and conservation attitudes on the development of the Bagek Kembar mangrove ecotourism area. The research employed a descriptive quantitative survey method. Respondents were selected using purposive sampling based on their involvement in tourism and conservation activities in the study area. Data were collected through structured questionnaires and analyzed descriptively, followed by multiple linear regression analysis to determine the relationship between variables. The results showed that the community’s level of conservation knowledge was categorized as low, with a percentage of 7.01%, while conservation attitudes were categorized as high, reaching 75%. The regression analysis indicated a positive relationship between conservation knowledge and conservation attitudes. Furthermore, partial statistical testing (t-test) and simultaneous testing (f-test) demonstrated that community knowledge significantly influenced conservation attitudes. These findings suggest that improving environmental education can strengthen community support for sustainable mangrove ecotourism management.